The Age Standardized Remission Rate of Acute Myeloid Leukemia in Adults - Hashmat, Sana; Bhutto, Sorath; Haider, Ghulam; Kumar, Krish; Qazi, SHAYAN ALI; Alam, Nargis; Qureshi, Areeba (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
This study was conducted to determine demographic distribution of Acute Leukemia (AL) among the adult patients in Pakistan. This was a cross-sectional survey conducted between September 2023 and February 2024 from the Department of Oncology at Jinnah Post-graduate Medical Center, Karachi Pakistan. This department receives cancer patients from all over the province of Sindh as well as from other provinces. A total of 130 adult patients with diagnosis of acute leukemia were included in this study. Participants were selected using convenient sampling technique. The median age of male AL patients was significantly higher as compared to females i.e. 30 years ;IQR=18 versus 24 years; IQR=21.25 years (p value= <0.05).There was statistically significant difference in the age distribution among AL patients between males and females. This study found male: female ratio of 1.8:1 among AL patients. No statistically significant difference was observed in the socio-demographic and disease-related characteristics among male and female. The current study concludes that acute leukemia demonstrates male predominance. The average age of presentation was comparatively lower among females as compared to males. However, sociodemographic and disease characteristics does not appear to be influenced by gender. Large scale studies are required to evaluate its influence on clinical outcome.